Dielectric property enhancement and environmental stability in (AlxCr0.05−x)Nb0.05Ti0.9O2 ceramics: influence of Al3+/Cr3+ ratio and Al3+ site preference - Porntip Siriya; Jurimart Wongsricha; Nutthakritta Phromviyo; Atchara Khamkongkaeo; Wirat Jarernboon; Pornjuk Srepusharawoot; Prasit Thongbai (Results in Physics, 2025)
The development of TiO2-based ceramics with enhanced dielectric properties and environmental stability is crucial for next–generation capacitor applications. In this study, (AlxCr0.05–x)Nb0.05Ti0.9O2 ceramics (x = 0, 0.005, 0.01, and 0.025) were synthesized to investigate the role of Al3+/Cr3+ ratio and Al3+ site preference on dielectric behavior. All sintered ceramics exhibited a single–phase rutile TiO2 structure with dense microstructures and uniform elemental distribution. Raman and structural analyses indicated the presence of oxygen vacancies in Cr0.05Nb0.05Ti0.9O2, which were significantly reduced upon Al3+ incorporation, suggesting a predominant interstitial occupation of Al3+. Partial substitution of Cr3+ with Al3+ improved densification and grain growth, likely due to interstitial diffusion. Although Cr0.05Nb0.05Ti0.9O2 showed a high dielectric permittivity (ε′ ≈ 60,500 at 1 kHz), it suffered from a high loss tangent (tanδ ≈ 0.3) and poor frequency and temperature stability. With increasing Al3+ content, ε′ remained above 104 while tanδ decreased below 0.1, and both frequency and temperature stability were greatly improved. The dielectric variation under 30–95 % RH was less than 4.2 %, and long–term aging over 5 years resulted in <1.2 % deviation, demonstrating excellent environmental stability. Impedance spectroscopy confirmed electrically heterogeneous microstructures composed of semiconducting grains and insulating grain boundaries, suggesting that the giant dielectric response arises from an interfacial polarization mechanism. These results highlight the promising potential of (AlxCr0.05–x)Nb0.05Ti0.9O2 ceramics for robust dielectric capacitor applications.